2009
DOI: 10.1590/s1808-86942009000500015
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose and insulin levels in patients with peripheral vestibular disease

Abstract: Met abolic disorders can cause dizziness. Aim: to study the prevalence of glucose and glucose-insulin alterations in patients with peripheral vestibular disorders by studying the four-hour glucose-insulin curve; to check at what time there was the highest prevalence of altered cases and whether the glucose and insulin curves together are better than the isolate glucose curve and fasting glucose curve. Materials and Methods: retrospective study, analyzing 81 four-hour glucose-insulin curves in patients with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
11
1
3
Order By: Relevance
“…These metabolic disorders can act as a principal etiological factor in vestibular dysfunction, as well as an aggravating factor of a pre-existing vestibular disorder. 9 We did not find statistical significance for patients with glucose intolerance in relation to the number of recurrences, compared to normal subjects. This finding may suggest that this degree of change in carbohydrate metabolism is not significant to the point of an association with the evolution of BPPV.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…These metabolic disorders can act as a principal etiological factor in vestibular dysfunction, as well as an aggravating factor of a pre-existing vestibular disorder. 9 We did not find statistical significance for patients with glucose intolerance in relation to the number of recurrences, compared to normal subjects. This finding may suggest that this degree of change in carbohydrate metabolism is not significant to the point of an association with the evolution of BPPV.…”
Section: Discussioncontrasting
confidence: 61%
“…8,9 Furthermore, the labyrinth is very sensitive to small changes in plasma insulin levels, due to the large number of insulin receptors present in the endolymphatic sac. 11 Based on these suggestive signs (i.e., that glucose metabolism may be associated to clinical pictures of benign paroxysmal positional vertigo), this study found some relations, such as: the hyperinsulinemic patient has a RR 4.6 times higher for BPPV recurrence, compared with the general population ---a statistically significant finding.…”
Section: Discussionmentioning
confidence: 99%
“…A intensa atividade metabólica da estria vascular é dependente de oferta otimizada de ATP para garantir o funcionamento da bomba de sódio e potássio e, assegurar concentrações iônicas adequadas na endolinfa da orelha interna. (SERRA et. al, 2009) GANANÇA et.…”
Section: Resultado E Discussãounclassified
“…al (2003, acrescenta que a resistência periférica à insulina e a hiperinsulinemia podem gerar alteração do metabolismo lipídico como hipertrigliceridemia.SAITO T et al (1986) igualmente citado no estudo, esclarece que os efeitos supostos do distúrbio metabólico lipídico são lesões das células ciliadas cocleares, experimentalmente verificado na monitorização da orelha interna sob ação de dietas hiperlipídicas. Sob o mesmo prisma, o hipotireoidismo deve também, ao lado das alterações do metabolismo de carboidratos, ser aventado frente uma dislipidemia SERRA et al (2009). define que além de causadores de distúrbios vestibulares, as disfunções metabólicas podem funcionar como agentes de piora de vestibulopatias pré-existentes.…”
unclassified
“…Metabolic dysfunctions are considered responsible for labyrinthine changes [1]. Metabolic disorders may act as the main etiological factor in vestibular dysfunction or as an aggravating factor in preexisting vestibular disease [2].…”
Section: Introductionmentioning
confidence: 99%